Utilisation of diagnostics in India: a rapid ethnographic study exploring context and behaviour. Issue 11 (26th November 2020) - Holloway, Bronwen; Mathur, Aditya; Pathak, Ashish; Bergström, Anna
Abstract : Objectives: To explore factors that influence behaviour in the utilisation of diagnostics by caregivers of sick children. Utilisation is defined as a caregiver assisting a child to get diagnostic tests done and return for follow-up of results. Understanding these experiences may help inform the development of interventions and implementation strategies to improve the use of diagnostics, thereby target treatment and optimise antibiotic use. Design: A rapid ethnographic qualitative study using 3 months of unstructured observations, 1 month of structured observations of diagnostic utilisation and 43 semi-structured interviews. Transcripts were coded and analysed using inductive thematic analysis. Findings were explored from a behavioural perspective through the lens of the 'Capability, Opportunity, Motivation and Behaviour' (COM-B) model for understanding behaviour. The multiple methods of investigation applied allowed for triangulation and cross-validation of the findings. Setting: The paediatric outpatient department of a teaching hospital in rural, central India. Participants: Caregivers of sick children attending the paediatric outpatient department who were sent for one or more diagnostic test. Results: Three key themes were identified that influenced caregivers' behaviour. Caregivers trusted and understood the importance of diagnostics but their acceptance wavered depending on the severity of illness and preference to treat their child directly with medicines. Caregivers struggled to access diagnostics, describing delays in testing, receiving results and follow-up, further complicated by travel time, distance and competing priorities such as work. Diagnostics were relatively cheap compared with other healthcare facilities however, the cost of the test, travel expenses and wages lost for missing work, were barriers to getting the tests done and returning for follow-up. Conclusions: Diagnostics are generally accepted and their purpose understood, however, the organisation of diagnostic services, direct and indirect costs hinder caregivers from using diagnostics. Improvements in accessibility and affordability may increase caregiver motivation to use diagnostics and return for follow-up.